Composite Materials: On the Molecular to Continuum Modeling of Fiber‐Reinforced Composites (Adv. Theory Simul. 4/2020). Issue 4 (7th April 2020) - Rege, Ameya; Patil, Sandeep P.
Abstract : A bottom‐up multiscale model approach for describing fiber‐reinforced composites is described by Ameya Rege and Sandeep P. Patil in article number 1900211 . In their model, the fibers (for example, carbon nanotubes) are modeled as Euler–Bernoulli beams and the particle matrix (for example, silica aerogel) is modeled as an elastic foundation.